The Development of Home Industry in Enhancing Community Income in Sekernan District, Muaro Jambi Regency Based on Sharia Principles - Yusuf, Maulana; Andriani, Beid Fitrianova; Sidik, Syaiful Amar (CV. Zabags Qu Publish, 2026)
This study aims to analyze the development of home industry as a means of improving community income in Sekernan District, Muaro Jambi Regency, within the framework of Sharia principles. The background of this research lies in the strategic role of household-based enterprises as pillars of local economic growth and instruments of community empowerment. The main objectives are to identify strategies for home industry development, examine challenges encountered, and explore the application of Islamic values in business practices. The research adopts a qualitative phenomenological approach, employing in-depth interviews, participatory observation, and documentation, with data analyzed through thematic triangulation. Findings reveal that home industry development is structured around five key management functions: planning based on local resources, participatory organization of work, communicative leadership, motivation rooted in family values and religious ethics, and disciplined control of quality and finance. These results highlight that business success is not solely dependent on technical production aspects but also on the integration of Sharia principles, which ensure sustainability and fairness. The contribution of this study lies in enriching the literature on community empowerment and Islamic economics, while offering practical recommendations for entrepreneurs and policymakers to strengthen managerial capacity and embed Sharia values in the advancement of micro and small enterprises.